Educational model for elementary school in Ketapang - Prijowuntato, Sebastianus Widanarto (Proceedings of International Conference on Research in Education, 2025)
Ketapang is one of the 3T areas (outermost, foremost, lagging), a district in West Kalimantan Province. Ketapang Regency faces many problems, including economic, social, infrastructure, health, and educational issues. In the field of education, many problems are faced by both teachers and students in implementing learning. This study aims to reveal the current state of education and identify suitable learning models for the Ketapang area, particularly in the interior. The research location covers the northern, central, and southern parts of Ketapang. The data sources in this study included priests, teachers, students, and parents. Data were obtained through interviews, documentary studies, and observations in the three regions. The data analysis used included 1) reduction of the data obtained, 2) presentation of the data, and 3) drawing conclusions. The study's results suggest that the ideal educational framework for Ketapang Regency should focus on fostering educators' empathy and sincerity, employing media to boost student understanding, rewarding students, and ensuring educators enforce discipline to enhance learning effectiveness.
Keywords: 3T areas; educational model; elementary school; Ketapang